PROSES BELAJAR TARI TUO’SUMANGE KELOR DI SANGGAR SENI SULAWESI ART - Zahra, Fatima Tuz; Jazuli, Muhammad; Raharjo, Eko (JURNAL IMAJINASI, 2025)
The purpose of the study was to analyze the learning process at the Sulawesi Art Studio, to find out the learning process applied by the choreographer to one of the dance choreographies from the choreographer to the members of the studio. The learning process is part of Management, namely the function of implementation. The learning process according to Bandura explains the social learning process in four stages of the process, namely: the attention process, the retention process, the motor reproduction process, and the motivational process. The learning process in non-formal education that is directly related to the community, one of which is the Sulawesi Art Studio located in Bone Regency, South Sulawesi. The learning process at the Sulawesi Art Studio with Bandura's theory, goes through four stages. The Attention Phase, informs students about the concept of dance, division of tasks or organization in a choreography project. The second stage of storage in memory (pretention phase) participants or members of the studio prepare information that has been recorded and heard directly, both commands and division of tasks. The Reproduction Phase begins to divide work and the process of composing dance movements from the process of exploration, improvisation and formation of movement. The Motivation phase provides motivation to student members, developing artistic skills and maintaining traditional culture in South Sulawesi.